2010
DOI: 10.4103/0377-4929.68293
|View full text |Cite
|
Sign up to set email alerts
|

Solid variant of papillary carcinoma of nipple: An under recognized entity

Abstract: Papillary lesions of the breast represent a heterogeneous group with differing biological behavior. Solid papillary carcinomas are uncommon tumors composed of circumscribed large cellular nodules separated by bands of fibrosis. Correct diagnosis is crucial but may be difficult, as many other benign and malignant lesions have similar histological appearances. Immunohistochemistry plays a useful role in their differentiation. We describe one such case of a solid variant of papillary carcinoma of the left nipple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…However, solid papillary carcinoma is a basically in situ carcinoma observed in the mammary gland tissue; thus, it is quite different from cutaneous invasive tumor of SCAND. All lesions in the above 3 reports were seen in the nipple of women but not in the areola of men, 8–10 which differs from the present male areolar case.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…However, solid papillary carcinoma is a basically in situ carcinoma observed in the mammary gland tissue; thus, it is quite different from cutaneous invasive tumor of SCAND. All lesions in the above 3 reports were seen in the nipple of women but not in the areola of men, 8–10 which differs from the present male areolar case.…”
Section: Discussioncontrasting
confidence: 47%
“…Three cases of solid papillary carcinoma arising in the nipple have been reported. [8][9][10] Solid papillary breast carcinoma can be included in the differential diagnosis of SCAND. However, solid papillary carcinoma is a basically in situ carcinoma observed in the mammary gland tissue; thus, it is quite different from cutaneous invasive tumor of SCAND.…”
Section: Discussionmentioning
confidence: 99%
“…SPC tends to manifest as a palpable breast mass with frequent nipple discharge; however, only 2 cases of SPC occurring in the nipple have been reported in English medical literature. 14,15 The first case was reported by Sundaram et al 14 The reported lesion was a subareolar mass measuring 3 × 2 cm in a 75-year-old woman. A mammography suggested that the tumor was in a subareolar area, but not in the nipple itself.…”
Section: Discussionmentioning
confidence: 99%
“…6 To our knowledge, only 2 previous reports of SPC in the nipple have been made. 14,15 In this article, we report the first case of invasive SPC in the nipple with an in situ component/intraductal extension of the tumor cells in the subareolar ducts, Pagetoid extension to the nipple skin, and lymph node metastases in an 82-year-old woman.…”
Section: Introductionmentioning
confidence: 99%